Resection of Primary Renal Leiomyosarcoma Involving the Inferior Vena Cava (IVC) with IVC Resection and Reconstruction - Khaled Alshawwa; Jamal Hijazi; Bashar Jaber; Haitham AlHassan; Thaer Abu-Amer; Riyad Salahaldeen; Omar Abu-Zaydeh; Riad Haddad (Case Reports in Surgery)
Renal leiomyosarcoma is a rare, aggressive tumor of the smooth muscles of the kidney. In our case, the tumor has special characteristics that made it highly challenging, as it involved major vessels and other adjacent vital structures. The rarity of the tumor type itself and the special challenging features we faced intraoperatively encouraged us to report the case including the management plan for R0 resection. Our patient is a forty-two years old previously healthy female, with vague nonspecific presenting complains, ended up with a major highly advanced surgery necessitating the need for vascular reconstruction of IVC. The surgery was performed by a multidisciplinary team of highly specialized surgeons in related fields. The surgery went well, and the outcome was promising. The patient was followed up for about four months later, with uneventful course.